An Analysis of Tourism Spending and Expenditure Satisfaction among Cultural Tourists at Phra That Phanom, Nakhon Phanom Province - Manee, Parichat; Poolsawat, Pilaiwan (Journal for Developing the Social and Community, 2025)
Background and Aims: This qualitative study, employing a phenomenological approach, aims to provide an in-depth understanding of spending and satisfaction among cultural tourists at Phra That Phanom, Nakhon Phanom Province. Its objectives are to investigate tourism spending patterns and satisfaction with each type of expenditure among visitors. Methodology: The research purposively sampled 42 Thai tourists, with 7 participants from each of Thailand’s 6 regions. Data was collected through in-depth semi-structured interviews and observation, then analyzed using thematic analysis. Results: Results revealed distinct spending patterns across regions; for instance, Northeastern tourists exhibited the lowest spending, while those from the South incurred the highest, reflecting the influence of distance and cultural context. Satisfaction with spending was consistently highest for merit-making and donations (42.86%), followed by travel expenses (35.71%) and offerings (11.91%), indicating a significant spiritual motivation. Key findings also include the phenomenon of "faith pilgrimage cycles," the emergence of hybrid tourism behavior, and the notable influence of social media on spending planning. This study not only expands the understanding of cultural tourist spending dynamics but also challenges the notion of tourism as a purely economic phenomenon, highlighting an exchange between physical resources and spiritual experiences or cultural connections. These insights are valuable for policymakers, entrepreneurs, and local communities in developing sustainable and responsible tourism.